Cytotoxic effect of dual fluorescent-labeled oncolytic herpes simplex virus type 1 on mouse tumorigenic cell lines - Shahriyar Abdoli; Farzin Roohvand; Ladan Teimoori-Toolabi; Sara Shayan; Mohammad Ali Shokrgozar (Wolters Kluwer Medknow Publications, 2019)
The increasing incidences of cancer at the global scale have recently resulted in the invention of various biotechnology approaches among which the oncolytic virotherapy is a new strategy for the treatment of multiple tumors. Herpes simplex virus (HSV) based vectors are one of the most studied oncolytic agents, worldwide. Moreover, syngeneic animal models are the principal parts of the oncolytic virotherapies investigation. The effects of a dual fluorescent γ34.5 deleted vector-HSV-GR- on three mouse tumor cell lines were studied in this work. We previously generated a dual fluorescent labeled oncolytic HSV-HSV-GR- (both copies of γ34.5 were inactivated by insertion of two distinct fluorescent dyes, GFP and mCherry) in our laboratory; subsequently, they were used as oncolytic viruses. The three 4T1, TC-1, and CT26 cell lines were infected with HSV-GR. The infection efficacy and the elimination potency of HSV-GR were analyzed by photomicrography and flow cytometry methods. HSV-GR showed a significant efficiency to infect the cell lines examined. Flow cytometry analyses demonstrated that HSV-GR infected 89.3%, 86.1%, and 92.4% of 4T1, TC-1, and CT26 cells, respectively. Moreover, propidium iodide (PI) staining of infected cells indicated that HSV-GR could kill 27.9%, 21.2%, and 21.3% of 4T1, TC-1, and CT26 cells, respectively. Interestingly, HSV-GR infected cells were capable of expressing both GFP and mCherry at the same time. The promising effects of the oncolytic virus HSV-GR in the mouse syngeneic tumor cell system have shed more light on the therapeutic potential of this anti-cancer approach.